CAPECITABINE AND IRINOTECAN AS FIRST- LINE CHEMOTHERAPY FOR PATIENTS WITH METASTATIC COLORECTAL CANCER - Deyan Davidov (Peytchinski Publishing, 2010)
Objectives: Capecitabine is an oral fluoropyrimidine carbamate that is at least as effective than Fluorouracil / Leucovorin as first- line treatment for patients with metastatic colorectal cancer /CRC/. The topoisomerase I inhibitor Irinotecan has shown consistent efficacy in chemotherapy- naive patients. The aim of this study was to determine the efficacy and tolerability of Capecitabine in combination with Irinotecan /XELIRI/ as first- line therapy in patients with advanced CRC. Methods: In the period 2007- 2009 twenty-one consecutive patients with metastatic CRC entered the study. The treatment schedule consists of Capecitabine 1250 mg/m2 p.o. twice daily for 14 days with a 7- day rest period and intravenous Irinotecan 180mg/m2 day 1 with repetition of courses every 21 days. Results: Overall response rate was 33,3%. Median time to progression and overall survival was 7,6 months and 15,6 months, respectively. The most common grade 3- 4 adverse events were diarrhea and neutropenia. There were no treatment- related deaths. Conclusion: These results indicate that XELIRI is a potentially feasible and clinically active regimen in patients with advanced CRC.